A Role of IL-17 in Rheumatoid Arthritis Patients Complicated With Atherosclerosis - Wang, Jiexin; He, Linxi; Li, Weihong; Lv, Shangbin (Frontiers in Pharmacology, 2022)
Rheumatoid arthritis (RA) is mainly caused by joint inflammation. RA significantly increases the probability of cardiovascular disease. Although the progress of RA has been well controlled recently, the mortality of patients with RA complicated with cardiovascular disease is 1.5–3 times higher than that of patients with RA alone. The number of people with atherosclerosis in patients with RA is much higher than that in the general population, and atherosclerotic lesions develop more rapidly in patients with RA, which has become one of the primary factors resulting in the death of patients with RA. The rapid development of atherosclerosis in RA is induced by inflammation-related factors. Recent studies have reported that the expression of IL-17 is significantly upregulated in patients with RA and atherosclerosis. Simultaneously, there is evidence that IL-17 can regulate the proliferation, migration, and apoptosis of vascular endothelial cells and vascular smooth muscle cells through various ways and promote the secretion of several cytokines leading to the occurrence and development of atherosclerosis. Presently, there is no clear prevention or treatment plan for atherosclerosis in patients with RA. Therefore, this paper explores the mechanism of IL-17 in RA complicated with atherosclerosis and shows the reasons for the high incidence of atherosclerosis in patients with RA. It is hoped that the occurrence and development of atherosclerosis in patients with RA can be diagnosed or prevented in time in the early stage of lesions, and the prevention and treatment of cardiovascular complications in patients with RA can be enhanced to reduce mortality.